Suhbah: Relasi Mursyid dan Murid dalam Pendidikan Spiritual Tarekat - Moh. Isom Mudin (TSAQAFAH, 2015)
Tarîqah (Indo: Tarekat) is generally a specific method adopted by sâlik by passing the maqâmat and ahwâl; feel the spiritual condition. The special meaning is a gathering of Sufis with various regulations and activities of spiritual education in it. The Sufi orders suspected to appear in the third century of Hijrah and reached its forms in the fifth century of Hijrah. As part of the models of Sufism, the purpose of the congregation is essentially the same as tasawwuf general purpose of achieving the degree of ihsan. To achieve this degree, a salik should take spiritual education in the form mujâhadah and intensely riyâdah. The Interactions of people involved in it arranged in suhbah principles. Murshid and murid as two driving element tarîqah, they have this special relationship. Mursyid existence in following tasawuf is a necessity, it’s position as a doctor and supervising the students passed the ocean toward haqîqah and tahaqquq level. While the Interaction processes begins with the competency owned mursyid. This requirement is to ensure that the educational process will be done completely by the rules. The inauguration of the relationship between murshid and students marked the initiation in the form of spiritual bai‘ah, wear khirqah as identity born of a sâlik. These processes on is based on main references; al-Qur'an, al Hadits, and the ulama who have authority. These rules are able to make the teachings of sufism institute tested throughout the ages. Thus achieving the main goals of spiritual education in the form of the station of ihsân is a necessity.